Angels in the White Cube? : Rhetoriken kuratorischer Unschuld bei der dOCUMENTA (13) - Buurman, Nanne (My University, 2015)
Taking curatorial disclaimers of authorship as a starting point, the article calls attention to the convergence of historical scripts of femininity epitomized by the Victorian Angel in the House and contemporary curatorial codes of modesty. Despite Brian O'Doherty's famous deconstruction of the White Cube's purity, self-effacing curatorial statements and normative demands to always put the artists first are still very widespread. Focussing on dOCUMENTA (13) as a case study, the article scrutinizes how Carolyn Christov-Bakargiev's denial of authorship by means of modest rhetorics and a camouflage of display were contradicted by the ways in which authority was nevertheless centered on the curator in more or less subtle ways. It argues that the powers of display and the politicization of the exhibition space were thereby neglected in favour of suggesting unmediated access to artists, objects and realities that speak for themselves, thus presenting the curator as a humble non-interfering hostess.
Keywords: Gender; Kunst; 700 Künste; Bildende und angewandte Kunst; Museum; Kuratorische Praxis